Copyright for archivists and records managers - Padfield, Timothy; Padfield, Timothy (London Facet, 2010)
Outlines copyright law in the UK with special reference to materials relevant to archive and records collections, notably unpublished works. This book also offers advice on rights in the electronic environment and the problems associated with rights clearance; and covers related areas such as moral rights and rights in databases.
Originality, in particular in new editions of old works -- International copyright and qualification by country of origin -- University staff, academics and students -- Crown and Parliamentary copyright, and public sector information -- Licences, assignments and contracts -- 'Orphan' works -- Exhibition -- Electronic signatures and declaration forms -- Records management -- Digital rights management systems -- Magistrates' courts -- Ordnance Survey maps -- Electoral registers -- Databases -- Performers' and artists' rights, registered designs and privacy.
Rev. ed. of: Copyright for archivists and users of archives / Tim Padfield. 2nd ed. 2004.
Keywords: Copyright -- Great Britain; Archives -- Law and legislation -- Great Britain